KNOWLEDGE LEVEL OF AGRICULTURAL EMPLOYEES IN SALAHUDDIN PROVINNE ON HOW TO KEEP THE ENVIRONMENT FROM POLLUTION - Tayeh , Sondos Jassim; Ghaidhaib, Ali Ahmed (Diyala Agricultural Sciences Journal, 2016)
This study aimed basically a determine in the level of knowledge of the staff farm in the province of Salah al-Din on how to keep the environment from pollution and is determined by estimating the knowledge level staff farm in four fields in general and the order of the main areas of the level of knowledge respondents, as well as determine the correlation between the level of knowledge respondents and each of the following independent factors (age, sex, education level, years of service, jurisdiction, upbringing). The search included all staff farm in the Agriculture Department of Salahuddin province and the people affiliate's (166) respondents, after the exclusion of the test sample initial amount (30) employees, in addition to the exclusion of the forms that have not completed their answers become the research sample includes 115 employees has surveyed and study the process all of their findings. Has been to obtain data for research by questionnaire included two parts: the first part: to ensure their characteristics and personal career, either Part II: has included a measure promising specially to measure cognitive level employees agricultural on how to keep the environment from pollution, and after ascertaining the veracity of the content and honesty virtual was measured steadiness way retail midterm, and then began the process of data collection, and after unloading data and classification have been processed statistically using the statistical analysis for the social sciences (SPSS), The results showed that the majority of respondents was their level of knowledge in the field of preservation of the environment from pollution moderate. He also explained that the field of water pollution may be issued the first place to the level of knowledge and soil contamination has come in the last place of the level of knowledge respondents. The results also showed that the variables (age, years of service) related to the knowledge level of respondents and variables (sex, level of education, competence, origination) do not have anything to do with the cognitive level.